God and the IRS : accommodating religious practice in United States tax law / Samuel D. Brunson. - Brunson, Samuel D. (Cambridge University Press, 2018)
Seventy-five percent of Americans claim religious affiliation, which can impact their taxpaying responsibilities. In this illuminating book, Samuel D. Brunson describes the many problems and breakdowns that can occur when tax meets religion in the United States, and shows how the US government has too often responded to these issues in an unprincipled, ad hoc manner. God and the IRS offers a better framework to understand tax and religion. It should be read by scholars of religion and the law, policymakers, and individuals interested in understanding the implications of taxation on their religious practices.